2018
DOI: 10.1007/s10339-018-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Wakeful resting and memory retention: a study with healthy older and younger adults

Abstract: Studies indicate that a brief period of wakeful rest after learning supports memory retention, whereas distraction weakens it. It is open for investigation whether advanced age has a significant effect on the impact of post-learning wakeful rest on memory retention for verbal information when compared to a cognitively demanding distraction task. In this study, we examined (1) whether post-learning rest promotes verbal memory retention in younger and older adults and (2) whether the magnitude of the rest benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 45 publications
2
26
5
Order By: Relevance
“…For instance, Varma et al () found no differences in forgetting rates when researchers asked participants to wakefully rest after encoding, compared with participants who worked on a two‐back task or even on a cognitively more effortful three‐back task. Similarly, Martini, Riedlsperger, Maran, and Sachse () found no differences between wakeful resting and task‐related cognitive engagement when they asked participants to encode texts in their second language, independent of whether participants were involved in a verbal (reading a newspaper article) or visuospatial (finding errors in pictures) filler task after encoding (see also Fatania & Mercer, ; Martini, Zamarian, Sachse, Martini, & Delazer, ). These results suggest that under certain conditions, task‐related cognitive and sensory engagement compared with wakefully resting do not differ in their impact on memory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Varma et al () found no differences in forgetting rates when researchers asked participants to wakefully rest after encoding, compared with participants who worked on a two‐back task or even on a cognitively more effortful three‐back task. Similarly, Martini, Riedlsperger, Maran, and Sachse () found no differences between wakeful resting and task‐related cognitive engagement when they asked participants to encode texts in their second language, independent of whether participants were involved in a verbal (reading a newspaper article) or visuospatial (finding errors in pictures) filler task after encoding (see also Fatania & Mercer, ; Martini, Zamarian, Sachse, Martini, & Delazer, ). These results suggest that under certain conditions, task‐related cognitive and sensory engagement compared with wakefully resting do not differ in their impact on memory.…”
Section: Discussionmentioning
confidence: 97%
“…found no differences between wakeful resting and task-related cognitive engagement when they asked participants to encode texts in their second language, independent of whether participants were involved in a verbal (reading a newspaper article) or visuospatial (finding errors in pictures) filler task after encoding (see alsoFatania & Mercer, 2017;Martini, Zamarian, Sachse, Martini, & Delazer, 2018). These resultssuggest that under certain conditions, task-related cognitive and sensory engagement compared with wakefully resting do not differ in their impact on memory.…”
mentioning
confidence: 84%
“…Previous research [1,5,36,37] maintained that younger participants tend to build stronger memory representations than older adults. This suggests that healthy older individuals should be more vulnerable to interference between encoding and retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Retroactive Interference (RI) occurs when new information processed after initial learning impairs the recollection of previously encoded material [1]. Several studies have reported that wakeful resting, between encoding and retrieval, minimises the likelihood of RI and improves verbal and non-verbal memory performance in healthy young adults [2,3] as well as in older people [4,5] and in amnesic patients [6][7][8][9]. Studies with rodents have replicated the benefits of minimal interference on memory task performance [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation